PELATIHAN PENGENDALIAN EMOSI (EMOSMART) PADA REMAJA YANG TINGGAL DI PANTI ASUHAN YATIM PUTRI AISYIYAH KOTTABARAT - Wulan Agustina, Mutmainah; Musslifah , Anniez Rachmawati (DEVELOPMENT: Journal of Community Engagement, 2025)
Teenagers living in orphanages are individuals who need attention, especially to get through their teenage years. Teenagers living in orphanages are required to be able to develop themselves without parental support and to continue to have good relationships with the surrounding community. The problem is that it is still often found that teenagers living in orphanages find it a little difficult to mix with their peers outside the orphanage and seem stiff in organizing. This makes emotional control training important for teenagers living in orphanages to get to know themselves better and be able to make the right decisions. The final result of this service is that participants are able to understand the training material and participants are very enthusiastic in participating in the question and answer discussion related to emotional control. Participants in this service are teenagers living in the Aisyiyah Kottabarat Orphanage, then to be able to communicate the results of this parenting with caregivers and the dormitory